Financial education for the disadvantaged? A review - Horst Entorf; Jia Hou (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
In contrast to the popularity of financial education interventions worldwide, studies on the economic effects of those interventions report mixed results. With a focus on the effect on disadvantaged groups, we review both the theoretical and empirical findings in order to understand why this discrepancy exists. The survey first highlights that it is necessary to distinguish between the concepts of, and the relationships between, financial education, financial literacy and financial behavior to identify the true effects of financial education. The review addresses possible biases caused by third factors such as numeracy. Next, we review theories on financial literacy which make clear that the effect of financial education interventions is heterogeneous across the population. Last, we look closely at main empirical studies on financial education targeted at the migrants/immigrants, the low-income earners and the young, and compare their methodologies. There seems to be a positive effect on short-term financial knowledge and awareness of the young, but there is no proven evidence on long-term behavior after being grown up. Studies on financial behavior of migrants and immigrants show almost no effect of financial education.
urn:nbn:de:hebis:30:3-466710
Keywords: G28; G41; I24; I25; I28; 330; Financial Education; Financial Literacy; Inequality; Program Evaluation